Effect of chitosan coating on the properties of nanoliposomes loaded with oyster protein hydrolysates: Stability during spray-drying and freeze-drying. (15th August 2022) - Ma, Yuyang; Xu, Jinjin; Jiang, Suisui; Zeng, Mingyong
Graphical abstract: Highlights: Loading of oyster hydrolysate into the chitosan-coated nanoliposomes was performed. The chitosan coating improves the physical stability and EE of the nanoliposomes. The chitosan coating delayed the release rate of OPH during the digestive process. The stability of nanoliposomes after spray/freeze drying was evaluated. Abstract: Oyster protein hydrolysate (OPH) has high bioactivity and excellent performance, but its application in food formulation is still limited due to poor flavor and instability. In the present study, OPH was prepared by enzymatic hydrolysis and loaded into nanoliposomes. Then, the effects of chitosan coating (0, 0.25, 0.5, and 1.0%) on the physical properties, stability, and antioxidant activity were evaluated. The results showed that 1% chitosan-coated nanoliposomes had high encapsulation efficiency (EE) and physical stability. Additionally, chitosan coating slowed the release rate of nanoliposomes and increased the retention rate of antioxidant activity of OPH. The stability of the uncoated/coated nanoliposomes in a maltodextrin matrix by spray/freeze drying was evaluated. FTIR spectrum showed that hydrogen bonds, hydrophobic, and electrostatic interactions had been formed between chitosan-coated nanoliposomes and maltodextrin. Chitosan coating significantly improved the physical stability and antioxidant activity retention of nanoliposomes during powder reconstitution.